An e-learning outreach program for public schools: Findings and lessons learned based on a pilot program in Makati City and Cabuyao City, Laguna, Philippines - Nuncio, Rhoderick V. (Animo Repository, 2020)
The E-Learning Outreach Program (ELOP) is a multisectoral, collaborative, and commitment-driven action research that focuses on providing relevant and useful computer and Internet literacy short courses for public elementary students. This study presents the critical action plans of setting up a pilot e-Learning station in Hen. Pio del Pilar Elementary School in Makati City and in Pulo Elementary School in Cabuyao City, Laguna, Philippines. The school's computer laboratory was converted to an E-Learning station with additional devices and technical support from De La Salle University (DLSU). The study aims to account for a process-based heuristic approach in laying down the different phases of the program, specifically to: (1) coordinate and orient parents, pupils, teachers and school administrators, (2) set-up an e-Learning environment (3) design and write course modules (4) assess learning skills and experience of pupils, and (5) evaluate the program based on research team's observation and results of the focus group discussion (FGD) with teachers and student-participants. In Pulo Elementary School, a pretest and posttests were conducted with results showing that the program has improved participants’ e-Learning knowledge and skills except for advance skills in hardware utilization. The participants also showed a strong positive attitude towards the ELOP. © 2020 Elsevier Ltd